2016
DOI: 10.1038/hdy.2016.53
|View full text |Cite
|
Sign up to set email alerts
|

Demographic history, current expansion and future management challenges of wild boar populations in the Balkans and Europe

Abstract: Wild boar (Sus scrofa), one of the most widespread wildlife species, has entered a stage of continuous growth in Europe, and could even be considered a pest species. We analysed microsatellite variability in 723 wild boars from across Europe, including the northern Dinaric Balkans. Our aims were: (1) to define the population structure of wild boars in the Balkans and its relation with other European populations; (2) to estimate effective populations sizes, levels of intra- and inter-population diversity, inbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 55 publications
7
37
1
Order By: Relevance
“…Higher average allele numbers were found by Ferreira et al [ 32 ] in 110 wild boars from Portugal: based on six markers, the allele numbers varied between three and 15, averaging 10.17. According to Velickovic et al [ 3 ] 9–29 alleles were found with an average of 19 alleles per locus, in a fairly large sample set from 13 countries all across Europe, which should be the reason for high diversity. In a study that included samples from 10 regions all across East-Asia Choi et al [ 33 ] found allelic diversities between 3.4 and 9.6 (average: 6.46) using 16 microsatellite markers on a total of 238 wild boars ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher average allele numbers were found by Ferreira et al [ 32 ] in 110 wild boars from Portugal: based on six markers, the allele numbers varied between three and 15, averaging 10.17. According to Velickovic et al [ 3 ] 9–29 alleles were found with an average of 19 alleles per locus, in a fairly large sample set from 13 countries all across Europe, which should be the reason for high diversity. In a study that included samples from 10 regions all across East-Asia Choi et al [ 33 ] found allelic diversities between 3.4 and 9.6 (average: 6.46) using 16 microsatellite markers on a total of 238 wild boars ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under the influence of the last glacial a strong decrease in numbers happened, but the Carpathian Mountains functioned as a refugia, thus many species, including wild boars found an area to survive here. When the ice age ended, these species rapidly recolonized the neighbouring areas and nowadays wild boars are widely distributed across Europe, Asia and Northern Africa [ 1 , 2 , 3 , 4 , 5 , 6 ]. Their population size has rapidly increased since the 1960′s: in Europe the 5-year growth rate varied between 1.40 and 1.73 from 1990 to 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Most genetic studies on the diversity or phylogenetics of wild boar were based on partial D-loop sequences of mitochondrial DNA (mtDNA; less than 7% of the whole mtDNA genome), or cytochrome b sequences (Fang & Andersson, 2006;Kusza et al, 2014;Larson et al, 2005;Ramíres et al, 2009;Scandura et al, 2008;Veličković et al, 2015Veličković et al, , 2016Vilaça et al, 2014), which occupies less than 7% of the whole mtDNA genome, sometimes in combination with another region (e.g., cytochrome b). Most genetic studies on the diversity or phylogenetics of wild boar were based on partial D-loop sequences of mitochondrial DNA (mtDNA; less than 7% of the whole mtDNA genome), or cytochrome b sequences (Fang & Andersson, 2006;Kusza et al, 2014;Larson et al, 2005;Ramíres et al, 2009;Scandura et al, 2008;Veličković et al, 2015Veličković et al, , 2016Vilaça et al, 2014), which occupies less than 7% of the whole mtDNA genome, sometimes in combination with another region (e.g., cytochrome b).…”
Section: Introductionmentioning
confidence: 99%
“…A factor that could affect the quality of analysis is the type of genetic marker used in any study. Most genetic studies on the diversity or phylogenetics of wild boar were based on partial D-loop sequences of mitochondrial DNA (mtDNA; less than 7% of the whole mtDNA genome), or cytochrome b sequences (Fang & Andersson, 2006;Kusza et al, 2014;Larson et al, 2005;Ramíres et al, 2009;Scandura et al, 2008;Veličković et al, 2015Veličković et al, , 2016Vilaça et al, 2014), which occupies less than 7% of the whole mtDNA genome, sometimes in combination with another region (e.g., cytochrome b).…”
Section: Introductionmentioning
confidence: 99%
“…Essential in a risk assessment are future dispersal predictions, its consequences and effective management strategies. Effective strategies to prevent wild boar impacts should be based on the understanding of factors driving population increase and colonisation of new areas by wild boar (Massei et al 2015, Veličković et al 2016. Reforestation, agricultural intensification and climate change have been found to be the main drivers of wild boar population growth (Saez-Royuela andTelleria 1986, Massei et al 2015).…”
mentioning
confidence: 99%